Exploring the Portrayal of Institutional Translators and Interpreters in the Republic of Ireland’s English-Language Print Media - Hoyte-West, Antony (Vertimo studijos, 2020)
Although the Republic of Ireland has been a member of the European Union for nearly five decades, the country’s first official language, Irish, was only recognised as an official EU language on 1 January 2007. However, a lack of appropriately qualified linguistic personnel means that the language is currently subject to a derogation on its use in the EU institutions, which is scheduled to be lifted in 2022. Interviews conducted previously with interpreters in the Republic of Ireland (Hoyte-West 2020a) noted that practitioners generally viewed media coverage of the derogation as contributing to a positive image of the translational professions within the EU context; however, further research needed to be carried out on the topic. Accordingly, this article looks at how institutional translators and interpreters have been depicted in the Republic of Ireland’s English-language print media from 2007 to 2019. Using data obtained through a qualitative content analysis of the country’s three major English-language newspapers, an overview of the current situation is provided through analysis of the attitudes and opinions expressed.
Keywords: status of Irish; institutional translators; institutional interpreters; media portrayal